2018
DOI: 10.1021/acs.jmedchem.8b00961
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Development of Glutaminase Inhibitors: Achievements and Future Directions

Abstract: It has been demonstrated that glutamine metabolism has become the main energy and building blocks supply for the growth and viability of a potentially large subset of malignant tumors. The glutamine metabolism often depends upon mitochondrial glutaminase (GLS) activity, which converts glutamine to glutamate and serves as a significant role for bioenergetic processes. Thus, recently, the GLS has become a key target for small molecule therapeutic intervention. Numerous medicinal chemistry studies are currently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 106 publications
(235 reference statements)
1
60
0
Order By: Relevance
“…GLS inhibition has been also found to be efficient in combination therapy. The inhibition of the anti-apoptotic protein BCL-2 integrates glutaminase inhibition [ 222 ]. Furthermore, it has been shown that highly invasive ovarian cancer cells have increased glutamine dependence compared to less invasive cells [ 223 ], and metastatic prostate tumors show increased dependence on glutamine uptake [ 223 ].…”
Section: The Warburg Effect and Tumor Therapymentioning
confidence: 99%
“…GLS inhibition has been also found to be efficient in combination therapy. The inhibition of the anti-apoptotic protein BCL-2 integrates glutaminase inhibition [ 222 ]. Furthermore, it has been shown that highly invasive ovarian cancer cells have increased glutamine dependence compared to less invasive cells [ 223 ], and metastatic prostate tumors show increased dependence on glutamine uptake [ 223 ].…”
Section: The Warburg Effect and Tumor Therapymentioning
confidence: 99%
“…JHU-083 is a newly synthesized prodrug of DON, which can be administered in an inert state and then be activated preferentially in the tumor microenvironment through enzymatic cleavage, thus alleviating the previously reported toxicity of DON (106,121). Other DON prodrugs such as Rais-5C and Nedelcovych-13d have also been reported (122)(123)(124). Unlike the glutamine mimetics, the allosteric inhibitors such as BPTES and CB-839, are selectively targeting glutaminase without disturbing other aspects of glutamine metabolism (25,124).…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 99%
“…Other DON prodrugs such as Rais-5C and Nedelcovych-13d have also been reported (122)(123)(124). Unlike the glutamine mimetics, the allosteric inhibitors such as BPTES and CB-839, are selectively targeting glutaminase without disturbing other aspects of glutamine metabolism (25,124). BPTES is now the most frequently used allosteric glutaminase inhibitor, which specifically inhibits kidney type glutaminase activity through the formation of an inactive complex (125).…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to inhibiting glutamine uptake, in the past decade, research has focused on the antitumor effects of inhibition of glutaminase (GLS), the enzyme responsible for hydrolytic deamidation of glutamine to glutamate in the first enzymatic reaction of glutaminolysis. There are many small molecules that in recent years have proven to be capable of inhibiting GLS [ 107 , 108 ], such as the naturally occurring molecules 6-diazo-5-oxy-L-norleucine, azaserine, and acivicin, and the synthetic compounds BPTES, 968 and CB-839 [ 109 ] ( Figure 4 ). Among these, the compound CB-839 is a noncompetitive GLS inhibitor able to inhibit the entry of substrates into the TCA cycle, thus reducing cell viability and cancer stemness, increasing chemosensitivity, and inducing apoptotic cell death in several cancer types [ 110 , 111 , 112 , 113 , 114 ].…”
Section: Targeting Mitochondrial Metabolism In Cancermentioning
confidence: 99%